PERLINDUNGAN HUKUM BAGI ANAK SEBAGAI KORBAN KEKERASAN FISIK YANG BERDAMPAK PSIKIS TERHADAP KEBERLANGSUNGAN PENDIDIKAN FORMAL ANAK - Wardatul Muchlisoh (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2020)
Violence that has a psychological impact on children's education is currently not clearly regulated in Indonesian law. The law only explains the various forms and rules regarding violence in general. Problems will occur when a child (student) experiences violence, be it physical, psychological, or sexual violence thathas an impact on the victim's psychological can not hold the perpetrator accountable, because if the case of violence is brought to the law, the perpetrator will only be subject to the article related to violence or visible wounds. As for the psychological impact felt by the victims there are no rules to sanction perpetrators of violence to be responsible for the psychological state of their victims. The purpose of writing this law is to know and analyze legal protection guarantees for children victims of physical violence that have psychological impact on the continuity of formal education of children and also to determine the appropriate form of legal protection for children victims of physical violence that have psychological impact on the sustainability of children's formal education . This legal writing uses a type of normative juridical and this study also uses a qualitative descriptive analysis method.Keywords: Legal Protection, Violence, Psychic, Children's Education